Defining the Plant Peroxisomal Proteome: From Arabidopsis to Rice - Kaur, Navneet; Hu, Jianping (Frontiers in Plant Science, 2011)
Peroxisomes are small subcellular organelles mediating a multitude of processes in plants. Proteomics studies over the last several years have yielded much needed information on the composition of plant peroxisomes. In this review, the status of peroxisome proteomics studies in Arabidopsis and other plant species and the cumulative advances made through these studies are summarized. A reference Arabidopsis peroxisome proteome is generated, and some unique aspects of Arabidopsis peroxisomes that were uncovered through proteomics studies and hint at unanticipated peroxisomal functions are also highlighted. Knowledge gained from Arabidopsis was utilized to compile a tentative list of peroxisome proteins for the model monocot plant, rice. Differences in the peroxisomal proteome between these two model plants were drawn, and novel facets in rice were expounded upon. Finally, we discuss about the current limitations of experimental proteomics in decoding the complete and dynamic makeup of peroxisomes, and complementary and integrated approaches that would be beneficial to defining the peroxisomal metabolic and regulatory roadmaps. The synteny of genomes in the grass family makes rice an ideal model to study peroxisomes in cereal crops, in which these organelles have received much less attention, with the ultimate goal to improve crop yield.